Synthesis and photoluminescent properties of new ceramidine derivatives - Park, Byung Sun; Lee, Sang Woo; Kim, In Tae; Tae, Jin Sung; Lee, So Ha (WILEY-BLACKWELL, 2012)
A series of new ceramidine derivatives 8af has been synthesized in 45 steps involving a Wittig reaction of ceramidonine with various triphenylphosphonium bromides. Their UV and photoluminescence (PL) properties are reported. The compounds showed medium to strong PL between 502 and 522 nm at a concentration of 1 x 10(-5) M CH2Cl2. (C) 2011 Wiley Periodicals, Inc. Heteroatom Chem 23:6673, 2012; View this article online at . DOI 10.1002/hc.20753
Keywords: ORGANIC ELECTROLUMINESCENT DEVICES; DIODES